2019
DOI: 10.3390/nu11112822
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Maternal Food Intake Frequencies and Associations with Gestational Diabetes: The Cambridge Baby Growth Study

Abstract: Previous studies have suggested that in the first decade of this century the incidence of gestational diabetes (GDM) in pregnancy rose worldwide. In the Cambridge Baby Growth Study cohort we observed that this temporal trend was associated with an index of multiple deprivation and reductions in indices of insulin secretion. Deprivation level was not directly associated with GDM, suggesting that the temporal trend may relate more to other factors linked to it, such as dietary composition. In this study we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Each of the pregnant women were given an extensive questionnaire at recruitment to fill in as pregnancy progressed (with assistance from trained research nurses if required) [ 9 ]. These questionnaires were collected by the research nurses after the birth of the babies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the pregnant women were given an extensive questionnaire at recruitment to fill in as pregnancy progressed (with assistance from trained research nurses if required) [ 9 ]. These questionnaires were collected by the research nurses after the birth of the babies.…”
Section: Methodsmentioning
confidence: 99%
“…Food frequency intakes were also collected from the pregnancy questionnaires [ 9 ]. As part of a section of the questionnaire about lifestyle, there was a short (specific) food frequency questionnaire which covered most of the major food and drink types.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that contributed the most to the differences in the composition of the gut microbiota in ketonuric women was Methanobrevibacter , which, when assessing metagenomic linkage groups, in a previously published metagenome-wide association study of GDM was found to be enriched in healthy controls [ 18 ]. The third paper in this Special Issue, predominantly related to the time in pregnancy before any diagnosis of GDM, was from Cambridge Baby Growth Study investigators [ 19 ]. In their contemporary birth and infancy growth cohort they, like many investigators in other studies, had noticed a temporal trend in the incidence of GDM [ 20 ].…”
mentioning
confidence: 99%
“…Using a food frequency questionnaire, with all its inherent limitations [ 21 ], they found that the food type most consistently tracking the previously observed trends was eggs. In fact, egg consumption appeared to be protective against GDM, although the effect size was small [ 19 ]. Egg consumption in isolation may not totally explain the associations; however, principal component analysis suggested that in this cohort it was positively linked to the consumption of fresh fruit and green vegetables, salad, yogurt and tap water, i.e., a “healthy” diet.…”
mentioning
confidence: 99%